Operações helitransportadas: análise das armas e equipamentos utilizados no tiro embarcado pelo CTA/MA - Silva, Augusto Aguiar da (2018)
Today, it is essential to know which weapons are suitable for the practice of an on-board police shot that will enhance the performance of police officers in cases where firearms are extremely necessary when boarding helicopters during air operations. The undeniable improvement of police tactics and techniques had been stimulated by the modernization of organized crime, demanding firm responses from the State, among them, the application of aerial means in confronting crime and not just search and rescue. The objective of this study is to identify the armaments used in the Air Tactical Center of the state of Maranhão and to analyze the state of these mechanisms taking into account the need to acquire new devices that, or presenting differentiated mechanisms and accessories of better quality, become suitable for the accomplishment of the military police shot boarded in helicopters, aiming at the accomplishment of the operational objective. For that, a research of an applied nature and exploratory character had been adopted as a methodological resource, through a bibliographical and documentary study, with the analysis of books, specialized periodicals, as well as technical information acquired within the Center itself, also with the collection and analysis of data collected with the application of a questionnaire to the police of this Operational Unit. There are several deadlocks regarding the efficiency of weapons and equipment offered to professionals within the Air Tactical Center, classified as obsolete by the interviewees, causing their dissatisfaction, as well as the lack of confidence in the apparatus. It was also noticed the need to establish a continuous on-board training routine, as a way to guarantee the effectiveness of police actions. Thus, the study showed that it is fundamental to acquire new weapons for the center, together with the inclusion and establishment of a training routine for the professionals of the Unit.